Urinary antibiotics concentrations, their related affecting factors and infant growth in the first 6 months of life: A prospective cohort study - Pianpian Fan; Qianwen Shen; Ouyang Du; Yuanzhi Chen; Weifeng Tang; Jinqian Ma; Rui Ma; Ting Zhang; Zhong-Cheng Luo; Zhiwei Liu; Fengxiu Ouyang (Ecotoxicology and Environmental Safety, 2023)
Antibiotic exposure even in low-dose could have potential adverse health effects, especially during early life. There is a lack of data on antibiotic burdens in early infancy. We aim to assess antibiotic exposure in infants from birth to 6 months of age, their related affecting factors and the association between antibiotic exposure and infancy growth. Urine samples were collected at ages of 3 days, 42 days, 3 months and 6 months from 197 term-born Chinese infants. A total of 33 representative antibiotics were measured by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Urinary antibiotics were detectable in 69.4%, 63.2%, 75.0% and 84.3% of infants at ages of 3 days, 42 days, 3 and 6 months, respectively. The dominant antibiotic categories detected were: Preferred as Veterinary Antibiotics (PVAs), Human Antibiotics (HAs), and Veterinary Antibiotics (VAs). The detectable rates were 30.6%, 45.8%, 58.9%, and 81.4% for PVAs, 34.1%, 20.8%, 28.6%, and 45.1% for HAs, and 36.5%, 12.5%, 6.3%, and 5.9% for VAs, at age 3 days, 42 days, 3 and 6 months, respectively. Urinary concentrations of HAs and preferred as human antibiotics (PHAs) in newborns at age 3 days were not associated with maternal intrapartum antibiotic prophylaxis. Similarly, no associations were observed between urinary antibiotics concentration and antibiotics use in infants at age 42 days or 6 months. The numbers and concentrations of urine detectable antibiotics were similar between infants with exclusive breastfeeding and infants fed with formula or mixed-feeding at all ages of 42 days, 3 and 6 months. At age of 42 days, infants in the low tertile of total antibiotics concentration or with one antibiotic detected had higher weight-for-length Z score and greater head circumference, compared to infants with no antibiotics detected. No associations were found between urinary antibiotics and any of the infant anthropometric measures at age 6 months. In conclusion, urinary antibiotics were detectable in most infants during the first 6 months of life, and PVAs, HAs and VAs were the most commonly detected antibiotics. This suggested the possibility of a foods-originated antibiotics exposure in children. No strong nor consistent associations were found between urinary antibiotic concentration and infant growth at the first six months of life. Still, attention is needed on the adverse health effect of early life exposure to antibiotics in future studies.